Hadith #273 - Sahih Muslim - Abu al-Malih (Sahih Muslim)
I am narrating to you a hadith which I would have never narrated to you had I not been in death-bed. I heard Allah’s apostle (ﷺ) say: A ruler who has been entrusted with the affairs of the Muslims but he makes no endeavors ( for the material and moral uplift) and does not sincerely mean (their welfare) would not enter Paradise along with them.
Grade: Sahih